EKOSOFI CANGKIR KERA DALAM CERITA RAKYAT “BANGLAS ANTARA RINTIS” KARYA HANG KAFRAWI DKK. - Fauzi, Mohd. (Jurnal Ilmu Budaya, 2020)
The research attempted to describe the ecosophy of “Cangkir Kera” in Riau Malay Folklore “Banglas Antara Rintis” written by Hang Kafrawi. The kind of research is library research and the method used was descriptive-qualitative. The data was collected by using simak method. The data analysis applies agih method with the deletion technique and the substitution technique. The data used was written language related to ecolinguistic in Banglas Antara Rintis written by Hang Kafrawi, et al. The result of the research shows that Allah SWT has given Malay the environment with various types of plants. One unique plant is “Cangkir Kera” which can be used as a medium of medicine for anyone who coughs. The old Malays use pure water in a “Cangkir Kera” to treat coughing and other kinds of disease. This way is a form of local Malay wisdom in utilizing their environment by always expecting help from Allah SWT.